Emissions of dioxins and furans during steam gasification of Automotive Shredder residue; experiences from the Chalmers 2-4-MW indirect gasifier - Maric, Jelena (Waste management (New York, N.Y.), 2020)
Copyright © 2019 Elsevier Ltd. All rights reserved.